WORD EXPLORATION AND THE MEANING OF EVALUATION IN THE HOLY QURAN (THEMATIC INTERPRETATION OF EDUCATION EVALUATION) - Anwar Taufik Rakhmat; Ari Farizal Rasyid (Universitas Pendidikan Indonesia, 2021)
This study is intended to find the meaning of education evaluation in an Islamic perspective studied through the Holy Quran. By using a qualitative approach, content analysis research methods and data analysis techniques with the maudhui interpretation, it is found that the meaning of evaluation in the Holy Quran is found in words which mean evaluation in the form of terms derived from the words, حَسَبَ, نَظَرَ, بَلَا and اِمْتَحَنَ totaling 150 verses. Of the four words in the Holy Quran, the researcher defines educational evaluation as